Laws of Catalytic Aromatization Reaction of C1-C4-Carbohydrates and Texture Characteristics of Catalysts - N I, Fayzullaev; S Yu, Bobomurodova (International Journal of Psychosocial Rehabilitation, 2020)
For the catalytic aromatization reaction of lower alkanes (MoO3)x ∙ (ZnO) in the catalytic system based on the study of the promoter properties of Zr and B (MoO3)x ∙ (ZnO)y ∙ (ZrO2)z ∙ (B2O3)k catalyst was selected and this catalyst studied some kinetic laws of the catalytic aromatization reaction of C1-C4-hydrocarbons. As a result of research, the content of propane is 98.2%; iso-butane-0.18%; butane-1.62% proved that the reaction yield and selectivity relative to aromatic hydrocarbons had the highest value when the mixture was catalytic aromatized, and at this time the conversion of the mixture was 95.4%, the yield of aromatic hydrocarbons was 66.5% and the relative selectivity of aromatic hydrocarbons was 69.7%. The texture characteristics of the catalysts obtained in the study are also given.